Identifikasi Unsur Hara Esensial Pada Tanah Pertanaman Nilam (Pogostemon cablin benth) Di Desa Kolongan-Atas Dua Kecamatan Sonder - Pioh, Diane Deibij; Kamagi, Yani Ezrah Bartolomeus; Kumolontang, Wiesje Junnieke Nathsuo (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2026)
Patchouli (Pogostemon cablin benth) is a tropical plant that is currently widely cultivated due to its important role in the essential oil industry or patchouli. Indonesia is one of the world's main producers of essential oils. It is estimated that around 9 to 12 of the total 70 types of essential oils produced come from Indonesia, making essential oils one of the economic assets with great potential for the Indonesian economy. The purpose of this study was to identify essential nutrients in patchouli planting soil in Kolongan Atas Dua Village, Sonder District, Minahasa. This village has seen an increase in patchouli farming since 2022. To increase patchouli production, soil fertility needs to be deepened. The method used was a survey method by taking soil samples from land that was not planted with patchouli, land that had just been planted with patchouli, land that had been harvested twice. Furthermore, quantitative soil analysis used laboratory soil analysis methods, namely the N Keldjal method, P Bray K Spectrometer, C-organic Walkey and Black and pH using a pH meter. Research results indicate that the pH ranges from 6.5 to 6.6, with a slightly acidic profile. N, P, K, and organic matter are moderate to low. Considering the soil conditions in the patchouli plantations in Kolongan Atas 2 village, fertilization is necessary to maintain soil quality.